Scrum Implementation in Development of Online Research Application - Sundara, Tri; Setiawan, Dilly; Subkhan, Farid; Kautsar, Fitrah Rahmat (The Indonesian Journal of Computer Science, 2022)
Researchers often need a way to obtain research data through an online survey. Therefore a web-based online research application could be developed to address these needs. By using Scrum methodology, the online research application was then developed in which some challenges were found such as consistency of logic between developers in a team, relationships between different user modules, and shared debugging, among others. The challenges could be addressed by compliance with Scrum best practices and standards.